Evaluasi Karakter Morfologi dan Agronomi 20 Genotipe Terong (Solanum melongena L.) Untuk Terong Berproduksi Tinggi - Fella Novita; Listy Anggraeni; Lita Soetopo; Cipto Nugroho; Catur Hermanto (Vegetalika, 2026)
Eggplant production in Indonesia is still low, so characterization is expected to increase eggplant production by referring to the diversity of planting materials and breeding program. The characterization of 20 eggplant genotypes collected in East Java aims to determine the differences in morphological characteristics to be used as alternative new superior planting materials. The research was conducted in June-December 2021 with RBD and observations on 17 qualitative and quantitative characteristics. The 20 eggplant genotypes observed had different characteristics. Clustering analysis showed that 20 genotypes were divided into four groups based on fruit shape. PCA results show that genotypes G1, P2, and P1 are high-yielding genotypes. Plant characteristics determining high production were fruit yield per plant and fruit diameter, which correlated with the characteristics of flower number, plant height, fruit base shape, fruit stalk length, seed weight, and seed diameter.